PENGARUH ECONOMIC VALUE ADDED (EVA), MARKET VALUE ADDED (MVA), ARUS KAS OPERASI DAN EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM - Maulana, Rio Dimas; Yusralaini, Yusralaini; Hanif, Rheny Afriana (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to assess the impact of Economic Value Added (EVA), Market Value Added (MVA), Operating Cash Flow, and Earning Per Share (EPS) on Stock Returns for companies listed in the LQ-45 Index on the Indonesia Stock Exchange from 2020 to 2023. The population includes all 67 companies in the LQ-45 Index during this period. A purposive sampling method was used to select 23 companies. Data was collected through documentation studies and analyzed using descriptive statistics, classical assumption tests, and multiple linear regression. The findings indicate that: Economic Value Added (EVA) does not affect Stock Returns, Market Value Added (MVA) has no impact on Stock Returns, Operating Cash Flow influences Stock Returns, and Earning Per Share (EPS) does not affect Stock Returns